PERAN INTEGRASI NILAI SOSIAL DAN EMOSIONAL DALAM PEMAHAMAN KONSEP MATEMATIKA - Evi Lusiana Dewi; Rohmad Wahid Rhomdani (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
Conceptual understanding is an important foundation in mathematics learning. This study aims to describe the application of social and emotional values ​​in mathematics learning and its impact on students’ conceptual understanding. The method used is descriptive qualitative with subjects of grade XI students at SMA Negeri 5 Jember. Data were obtained through interviews, observations, and documentation of student worksheets. The results of the study indicate that the integration of values ​​such as empathy, cooperation, and open communication can create a positive and inclusive learning atmosphere. This has an impact on increasing student participation, self-confidence, and the ability to understand and explain mathematical concepts in a more structured manner. Thus, the social-emotional approach has been proven to strengthen the effectiveness of mathematics learning and become an alternative learning strategy that is humanistic and meaningful.